Lung function in pulmonary hypertension. Issue 10 (October 2015) - Low, A.T.; Medford, A.R.L.; Millar, A.B.; Tulloh, R.M.R.
Abstract: Breathlessness is a common symptom in pulmonary hypertension (PH) and an important cause of morbidity. Though this has been attributed to the well described pulmonary vascular abnormalities and subsequent cardiac remodelling, changes in the airways of these patients have also been reported and may contribute to symptoms. Our understanding of these airway abnormalities is poor with conflicting findings in many studies. The present review evaluates these studies for the major PH groups. In addition we describe the role of cardiopulmonary exercise testing in the assessment of pulmonary arterial hypertension (PAH) by evaluating cardiopulmonary interaction during exercise. As yet, the reasons for the abnormalities in lung function are unclear, but potential causes and the possible role of inflammation are discussed. Future research is required to provide a better understanding of this to help improve the management of these patients. Highlights: Studies of lung function in pulmonary hypertension are conflicting. We review the lung function abnormalities associated with pulmonary hypertension. Breathlessness and reduced exercise tolerance is common in pulmonary hypertension. The cause and impact of abnormal lung function on symptoms is poorly understood. Further research may identify novel targets for dyspnoea in pulmonary hypertension.